Recruited / Suzanne Weyn. - Weyn, Suzanne (Minneapolis : Darby Creek, 2011)
Kadeem Jones is a star quarterback for Southside High. He is thrilled when college scouts seek him out. His visit to Teller College is amazing, but then NCAA officials accuse Teller's staff of illegally recruiting top talent. Will Kadeem decide to help their investigation, even though it means the end of the good times? What will it do to his chances of playing college football?
Accelerated Reader AR
Keywords: Football stories; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction; Football players -- Fiction; College athletes -- Recruiting -- Juvenile fiction; College sports -- Corrupt practices -- Juvenile fiction